The standardized Jamu pahitan, an Indonesian antidiabetic formulation, stimulating the glucose uptake and insulin secretion in the in-vitro models - Hartanti D. (2023)
Jamu pahitan is a polyherbal formulation commonly used for the traditional management of diabetes in Indonesia and is mainly prepared from Andrographis paniculata (Burm.f.) Nees. It is widely varied in herbal composition for every region has their own plant component addition to the formulation. A version of the formulation used in the greater Surakarta area contained five plant constituents. This study evaluated the in-vitro glucose uptake and insulin secretion stimulatory activities of Jamu pahitan to provide scientific evidence on its efficacy and safety of use. The water and ethanol extracts of three Jamu pahitan formulations were prepared. The total phenolic content (TPC) of the extracts was evaluated by the standard Folin-Ciocalteau method. Their effects on the viability of L6 skeletal muscle and RIN-m5F pancreatic cells were evaluated by a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. The glucose utilized by L6 myotubes treated with Jamu pahitan was assessed indirectly by the glucose oxidase method. The insulin secreted by RIN-m5F treated with the formulation extracts was analyzed by the enzyme-linked immunosorbent assay (ELISA). The correlation between TPC and the profile of safety and efficacy of the formulation was statistically evaluated. The water extracts of Jamu pahitan were safe and exerted significant glucose uptake and insulin secretion stimulatory activity in L6 and RIN-m5F, respectively. The ethanol extracts showed more potent effects than their water counterpart, albeit they exerted cytotoxic effects on the cells at the higher tested concentrations. The formulations at lower concentrations stimulated the proliferation of RIN-m5F. In addition, the TPC was strongly correlated with the glucose uptake and insulin secretion stimulatory activities and also the IC50 of the cells in positive manner. The present study supported the use of Jamu pahitan for the traditional management of diabetes in Indonesia by stimulating glucose uptake in the muscle cells and improving insulin secretion in β-cells.